Tumor immune microenvironment characteristics of papillary thyroid carcinoma are associated with histopathological aggressiveness and BRAF mutation status. Issue 8 (21st March 2019) - Means, Casey; Clayburgh, Daniel R.; Maloney, Lauren; Sauer, David; Taylor, Matthew H.; Shindo, Maisie L.; Coussens, Lisa M.; Tsujikawa, Takahiro
Abstract: Background: Papillary thyroid carcinoma (PTC) follows an indolent course; however, up to 30% of patients develop recurrent disease requiring further treatment. Profiling PTC immune complexity may provide new biomarkers for improved risk prediction. Methods: Immune complexity profiles were quantitatively evaluated by multiplex immunohistochemistry (mIHC) in archived tissue sections from 39 patients with PTC, and were assessed for correlations with aggressive histopathological features based on the presence of lymphovascular invasion and/or extrathyroidal extension, and BRAF V600E mutational status. Results: mIHC revealed two distinct immune clusters stratifying patients: a lymphoid‐inflamed group (higher CD8 + T cells, reduced dendritic and mast cells) and a myeloid/hypo‐inflamed group that correlated with aggressive pathological features. BRAF mutation was not associated with aggressive pathological features but did correlate with increased mast cell density. Conclusions: Distinct immune microenvironments exist in PTC correlating with pathological aggressiveness. Immune‐based biomarkers associated with possible tumor‐immune interactions may be used for risk stratification.